Android-Based Learning Media for Water Introduction - Anang Qosim (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The purpose of this study is to assess the practicality of a water introduction learning tool based on Android, as evaluated by experts in the field of materials and media. The research aims to provide insights into the effectiveness of the Android-based product in facilitating effective learning and understanding of the concept of water introduction. Materials and methods. The research method utilized in this study is Research and Development, while the technique applied is also Research and Development. The purpose of this research was to create and assess the feasibility of Android-based learning materials and media. The development process in this research followed the steps defined by Sismadiyanto et al. The product validation subject was the primary focus of this development research. Material experts and media experts were the ones who took part in the product validation test. The models in this research were the students of Penjaskesrek Semester IV. Various data collection methods were employed to gather data, including initial condition data and expert test results data. The data collection methods used in this research were defined as follows: (1) observation techniques to obtain water introduction learning media, (2) interview techniques to obtain initial condition data, and (3) questionnaire/questionnaire techniques to obtain development data products from material experts and media experts. Results. The Android-based water introduction learning media has been validated by material and media experts. The material expert validation resulted in an average score of 4.64 which falls in the outstanding category. The aspect of material relevance was rated as good. On the other hand, the media expert validation resulted in an average score of 4.67 in the very good category for the software engineering aspect. The visual communication aspect was rated 4.33 on average, also falling in the very good category. Conclusion. According to the findings of a recent research study, it has been observed that Android-based water introduction learning media products are highly effective and incredibly suitable for use as a primary teaching aid in swimming lessons. These products are carefully designed to provide a comprehensive and engaging learning experience, which helps learners master the basic skills of swimming safely and efficiently. The study also suggests that these Android-based learning media products can be used to supplement traditional teaching methods and can help learners to develop a strong foundation in swimming, which can enhance their overall swimming abilities.